Applying psychology to work - Aamodt, Michael G. (Wadsworth/Cengage Learning, 2013)
Striking a balance between research, theory, application, this book helps students discover the relevance of industrial of industrial/organizational psychology in everyday life through practical application as they analyze topics such as resume writing, interview survival, job description authoring and performance appraisal